"Harry Potter": One of the Best Book Series Ever - Ridha, Muhammad Rasyid (Linguistika Kultura, 2023)
This study aims to explain why "Harry Potter" can be considered one of the best book series ever made. There is much debate on why literature and movie fans love "Harry Potter." This essay will analyze and describe a few important reasons for that topic. To answer this question, I used descriptive analysis to describe and analyze the reasons. My result describes a few things that can be the reason this book series can be one of the best book series ever made. For a few reasons, "Harry Potter" is detailed and full of content that makes readers enjoy reading it. Also, "Harry Potter" has some impact on people worldwide that can influence people's lives. The reasons in this essay informed people and gave people answers to why "Harry Potter" is considered one of the best book series ever made.